Associations Among Methylene Tetrahydrofolate Reductase rs1801133 C677T Gene Variant, Food Groups, and Non-alcoholic Fatty Liver Disease Risk in the Chinese Population - Hao, Xiaoyan; Ma, Cong; Xiang, Tianyuan; Ou, Lei; Zeng, Qiang (Frontiers in Genetics, 2021)
Objectives: To investigate the associations among the methylene tetrahydrofolate reductase rs1801133 C677T gene variant, food groups, and the risk of nonalcoholic fatty liver disease in the Chinese population. Methods: A study of gene polymorphism was conducted using the polymerase chain reaction method. A total of 4049 adults participated in the study, and all underwent physical examination and genotyping. Participants filled out a dietary questionnaire to enable us to assess the frequency and quantity of food consumption. . Results: The important variables identified as risk factors of nonalcoholic fatty liver disease were age, smoking, sex, body mass index, hyperlipidemia, diabetes, and methylene tetrahydrofolate reductase genotype (T - allele carriers). The homocysteine content was higher in the nonalcoholic fatty liver disease group than in the control group, and was higher in the T- allele than C- allele carriers. The homocysteine content was the highest in the T- allele carriers. Additionally, certain food groups such as milk and beans were associated with a lower risk of nonalcoholic fatty liver disease. Food groups such as meat, were associated with a higher risk of nonalcoholic fatty liver disease. Fresh fruit and vegetables, salted and smoked foods, desserts, cereals, fish and eggs were not associated with the risk of nonalcoholic fatty liver disease. However, the influence of salted and smoked foods on nonalcoholic fatty liver disease was different in the C-allele and T-allele carriers of methylene tetrahydrofolate reductase(CT + TT vs CC, OR = 1.196, P = 0.041 for 1–4times food per week. OR = 1.580, P = 0.004 for 5–7 times per week). Similarly, salted and smoked foods were also a risk factor for the development of nonalcoholic steatohepatitis in patients with nonalcoholic fatty liver disease. Conclusion: This study found that the T-allele of the C677T variant of methylene tetrahydrofolate reductase was a risk factor for nonalcoholic fatty liver disease among Chinese people. These results can likely aid the development of novel approaches for managing nonalcoholic fatty liver disease risk.